Determinants of market driven companies: a study on small enterprises operating in the heritage conservation zone of little India, Penang - Nagoorgany, Mahmudah (2004)
The small enterprises (SEs) operating in the heritage conservation zone of Penang encounter challenges internally and externally in their operation such as financial constraints, and competitors’ threat. They also need to comply with the rules and regulations imposed by the local authorities concerning the area. As it is proven that market driven strategy enhance company performance, the small enterprises in the heritage conservation zone should develop market driven behavior to face the challenges.